Implementation of Radiant Cooling System in Floors - Ghosh, A. Prabu Kumar; Loganathan, A.; Naveenraj, N.; Prakash, P.; Balakrishnan, N. (International Journal For Research In Mechanical & Civil Engineering, 2017)
Taking energy crisis into consideration many researches are going on in alternative sources in the fields of Automobile, Refrigeration and Air Conditioning, Oil and Gas Industries. Radiant cooling system is such a type of alternative source used in the field of Air conditioning systems. Radiant cooling system can be implemented in floors, ceilings and pillars of multi storey buildings. We have implemented radiant cooling system in floors. With this system surrounding surface temperatures are lowered by absorbing the sensible heat from the conditioned space providing thermal comfort to the occupants in the room and this is made by circulating cooling water in the floors through copper/ aluminium tubes.